The representation of “The myth of Sisyphus” by Albert Camus in the information retrieval dictionary model of ancient Greek mythology - Antoniuk, H. D.; Kulchutzkyj, I. M.; Антонюк, Г. Д.; Кульчицький, І. М. (Східноєвропейський національний університет ім. Лесі Українки, 2011)
The article investigates evolution of the image of the mythological character Sisyphus in the Greek mythology and in the modern European literature on the example of philosophical essay of the French writer Albert Camus “Myth about Sisyphus”. On the basis of theoretical material with the help of corpus linguistics means (text corpora) the attempt to develop information model of dictionary of the old Greek mythology has been made. The purpose of the dictionary model is further studying and research of the Greek mythology. У статті простежено еволюцію образу міфологічно- го героя Сізіфа в давньогрецькій міфології і в сучасній європейській літературі на прикладі твору французь- кого письменника Альбера Камю “Міф про Сізіфа”. На основі теоретичного матеріалу за допомогою засобів корпусної лінгвістики зроблено спробу розробити інформаційну модель словника давньогрецької міфології задля подальшого наступного дослідження та вивчення давньогрецької міфології.
Репрезентація твору А. Камю “Міф про Сізіфа” у інформаційно- пошуковій моделі словника давньогрецької міфології”
Keywords: myth; mythology; corpus linguistics; information model of dictionary; міф; міфологія; корпусна лінгвістика; інформаційна модель словника